Idiosyncratic Risk Matters: An Empirical Investigation of UK Equity Market - Zhuge, Yun (2010)
Our empirical study is an extension of idiosyncratic volatility investigation in UK market through the utilization of the decomposition model of Campbell, Lettau, Malkiel and Xu (2001). The framework of Campbell et al (2001) helps our investigation into three levels, which are market level, industry level and firm level. The empirical results of our study are as follows. Firstly, firm idiosyncratic volatility contains a significant increasing deterministic trend, but only a comparatively smaller trend could be found in market level. In terms of industry level volatility, no trend could be implied for aggregate industry volatility; however, intra-industry studies have addressed various behaviours of firm volatility and industry volatility across industries. Secondly, more assets are required to be added into a portfolio recently to diversify the risk to the level of early period. Thirdly, our study reports a granger causing role of industry level volatility to other two series, and a lead-lag relation between firm level volatility and market volatility through Granger-Causality test. In addition, the firm level volatility accounts the largest component of total volatility and variance across time. Fourthly, three components of volatility behave fairly countercyclical and aggregate volatility tends to help forecast the growth of GDP. These behaviours related results improve the importance of economic cycle. Under the robustness checks, firm level volatility shows a significant negative forecasting ability of equity return.